Transcriptomic and proteomic analysis reveals the mechanism of chicken cecum response to Salmonella enterica serovar Enteritidis inoculation - Yuanmei Wang; Liying Liu; Yanan Zhao; Yanru Ren; Xiuxiu Miao; Yaning Dong; Lewen Liu; Xianyao Li (iScience)
Summary: Salmonella enterica serovar Enteritidis (SE) incurs foodborne illnesses and poses a severe threat to poultry industry and human health. However, the molecular mechanisms underlying chicken responding to SE inoculation remain elusive. Here, we characterized the transcriptome and proteome of chicken cecum 3 days post SE inoculation. Totally, there were 332 differentially expressed genes and 563 differentially expressed protein identified. The upregulated genes were enriched in immune-related processes. The downregulated proteins mainly correlated with metabolic process. The correlation coefficient between the transcriptome and proteome was 0.14. Collectively, we characterized the landscape of mRNAs and proteins in chicken cecum following SE inoculation and found SE inoculation induced chicken immune system at transcriptomic level but impaired the metabolism at protein level. The differences may be caused by complex post-transcriptional regulatory mechanisms or time-dependent delays. Our findings would extend the understanding of the molecular mechanisms underlying chicken responding to SE inoculation.